2016
DOI: 10.1093/cvr/cvw166
|View full text |Cite
|
Sign up to set email alerts
|

The endothelial adrenomedullin-RAMP2 system regulates vascular integrity and suppresses tumour metastasis

Abstract: These findings indicate that the AM-RAMP2 system regulates vascular integrity, whereas RAMP2 deletion promotes vascular permeability and EndMT-like change within primary lesions and formation of pre-metastatic niches in distant organs by destabilizing the vascular structure and inducing inflammation. Vascular integrity regulated by the AM-RAMP2 system could thus be a hopeful therapeutic target for suppressing tumour metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 37 publications
0
42
2
Order By: Relevance
“…A constitutive flow-dependent autocrine or paracrine mechanism is also indicated by our observation of strong defects in fluid shear stress-induced cellular effects in isolated endothelial cells with suppressed adrenomedullin and adrenomedullin receptor expression as well as in flow-induced vasodilation in vessels isolated from endothelium-specific CALCRL-and adrenomedullin-deficient mice. Flow-induced adrenomedullin-dependent cAMP production and eNOS activation may also be critically involved in other adrenomedullin functions that have been shown to require endothelial adrenomedullin release and functional endothelial adrenomedullin receptors, such as angiogenesis and maintenance of endothelial barrier function (61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…A constitutive flow-dependent autocrine or paracrine mechanism is also indicated by our observation of strong defects in fluid shear stress-induced cellular effects in isolated endothelial cells with suppressed adrenomedullin and adrenomedullin receptor expression as well as in flow-induced vasodilation in vessels isolated from endothelium-specific CALCRL-and adrenomedullin-deficient mice. Flow-induced adrenomedullin-dependent cAMP production and eNOS activation may also be critically involved in other adrenomedullin functions that have been shown to require endothelial adrenomedullin release and functional endothelial adrenomedullin receptors, such as angiogenesis and maintenance of endothelial barrier function (61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…However, since these genes are not endothelial-specific, the contribution of these genes in endothelial cells to pre-metastatic niche formation still remains unclear. A recent study demonstrated that endothelial cell-specific overexpression of receptor activity modifying protein 2 (RAMP2), a receptor for a hormone adrenomedullin, improves vascular integrity and is protective against metastasis of sarcoma and melanoma in mice [ 35 ]. We also previously showed that ANP inhibits LPS-induced inflammation through down-regulation of E-selectin, resulting in reduced metastasis of melanoma cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also the role of the ADM–RAMP 2 system has been investigated. Mice lacking the gene encoding for RAMP 2 showed enhanced vascular permeability and systemic oedema . Similarly, mice with a conditional knock‐out of ADM in endothelial cells revealed increased vascular permeability in comparison with wild‐type littermates …”
Section: Vascular Effects Of Adrenomedullinmentioning
confidence: 96%
“…Mice lacking the gene encoding for RAMP 2 showed enhanced vascular permeability and systemic oedema. 36 Similarly, mice with a conditional knock-out of ADM in endothelial cells revealed increased vascular permeability in comparison with wild-type littermates. 39 Further support for the effects of ADM in maintaining vascular integrity comes from experimental studies showing that experimental overexpression of ADM inhibits systemic and pulmonary vascular leakage in animals.…”
Section: Vascular Effects Of Adrenomedullinmentioning
confidence: 98%
See 1 more Smart Citation